Internalization of Akkarungeng Values in The Election of Regional Heads in The Community in Bone Regency - Suhartono Firman; Sukri Sukri; Ariana Ariana (Publik : (Jurnal Ilmu Administrasi), 2021)
Internalization of akkarungeng values in the election of regional heads in the community in Bone Regency. Research method with qualitative approach. This article describes and analyzes the internalization of akkarungeng values in Bone Regency in the regional head election. The method used is a research method with the type of qualitative research. The approach used is a political science and juridical approach. The location of this research is Bone Regency, South Sulawesi, Indonesia with data collection techniques including observation, interviews and documentation. The data analysis technique includes three stages, namely data reduction, presentation and conclusion drawing. Validity testing is done by using data triangulation. The results of this study indicate the values of akkarungeng such as getteng, lempu, ada tongeng, sipakatau and temmapasilaingeng owned by a nobleman so that they are still chosen by the community to become a leader. The tendency of the nobility to then carry out a strategy to continue their leadership line by internalizing the values of akkarungeng in the children of noble descent so that they are able to take the sympathy of the community to become leaders in the community. In addition, support for access to education is also one of the supporters to get the intelligence and advice of their ancestors that makes them have the character of courage.